Kinerja Lalu Lintas Simpang Tak Bersinyal Perkotaan pada Lahan Terbatas (Studi Kasus : Simpang Jl. M. Kahfi II – Jl. Srengseng Sawah, Jakarta Selatan) - Endang Widjajanti; Wileri Mandabi; Lely Mustika (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
Abstract This study aims to determine the performance of the unsignalized intersection Jl. M. Kahfi II – Jl. Srengseng Sawah, South Jakarta. The analysis of the performance at unsignaled intersections refers to the guideline of the Indonesian Road Capacity Manual (MKJI), 1997. Data obtained through field surveys include geometric conditions, environmental conditions, and traffic conditions. The results of the analysis show that the peak hours of the working day in the morning period occur at 06.30 – 07.30 with a degree of saturation (DS) 1.10 with an intersection delay (D) of 25.16 sec/pcu and the afternoon period occurs at 18.00 – 19.00 with a degree of Saturation (DS) 0.93 with Intersection Delay (D) 16.39 sec/pcu. The results of the analysis for holidays show that the peak hours of the morning holiday period occur at 08.00 – 09.00 with a Degree of Saturation (DS) 0.71 with a Intersection Delay (D) 11.74 sec/pcu and the afternoon period occurs at 16.45 – 17.45 with a degree of saturation (DS) 0.85 with an intersection delay (D) of 14.31 sec/pcu. The results of this analysis indicate that the performance of the unsignalized intersection on Jl. M. Kahfi II – Jl. Srengseng Sawah South Jakarta is already in bad condition on weekdays and not good on holidays.. Increasing the capacity of Jalan Kahfi II in accordance with detailed spatial plans and zoning regulations in the Jagakarsa District, South Jakarta City in 2014, namely an increase in Jl. Kahfi II from Road Type 2/2 UD to 4/2D is very urgent to apply Keywords: traffic performance, urban, unsignalized intersection